# Raising a Power to Another Power

If we are given $(2^3)^4$, that can be written in factor form as $2^3 \times 2^3 \times 2^3 \times 2^3$.
We can then simplify the multiplication using the exponent’s rule as $2^{3+3+3+3} = 2^{12}$.

Similarly, if we are given $(5^2)^3$, this means;
\begin{align} (5^2)^3 &= 5^2 \times 5^2 \times 5^2 \\ &= 5^{2+2+2} \\ &= 5^6 \end{align}

Using the above method we can see that $(2^3)^4 = 2^{12}$ and $(5^2)^3 = 5^6$.

You will notice that
\large \begin{align} (2^3)^4 &= 2^{3 \times 4} = 2^{12} \\ (5^2)^3 &= 5^{2 \times 3} = 5^6 \end{align}

When raising a power to another power, we multiply the exponents (indices).
$$\large (a^x)^y = a^{x \times y}$$

This rule also implies;
\large \begin{align} (a \times b)^x &= a^x \times b^x \\ \Big(\dfrac{a}{b}\Big)^x &= \dfrac{a^x}{b^x} \end{align}

### Example 1

Simplify $(6^3)^3$.

\begin{align} \displaystyle (6^3)^3 &= 6^{3 \times 3} \\ &= 6^9 \end{align}

### Example 2

Simplify $(ab^4)^3$.

\begin{align} \displaystyle (ab^4)^3 &= (a^1b^4)^3 \\ &= a^{1 \times 3} b^{4 \times 3} \\ &= a^3b^{12} \end{align}

### Example 3

Simplify $(2a^3b^2)^3$.

\begin{align} \displaystyle (2a^3b^2)^3 &= 2^3 a^{3 \times 3} b^{2 \times 3} \\ &= 8a^9b^{6} \end{align}

### Example 4

Simplify $(2x^3)^2 \times (3x^5)^3$.

\begin{align} \displaystyle (2x^3)^2 \times (3x^5)^3 &= 2^2 x^{3 \times 2} \times 3^3 x^{5 \times 3} \\ &= 4x^6 \times 27x^{15} \\ &= (4 \times 27) \times x^{6+15} \\ &= 108x^{21} \end{align}

### Example 5

Simplify $\Big(\dfrac{2a^3}{b^2}\Big)^3$.

\begin{align} \displaystyle \Big(\dfrac{2a^3}{b^2}\Big)^3 &= \dfrac{(2a^3)^3}{(b^2)^3} \\ &= \dfrac{2^3 a^{3 \times 3}}{b^{2 \times 3}} \\ &= \dfrac{8 a^9}{b^6}\ \end{align}